Onset of meso-scale turbulence in active nematics - Amin Doostmohammadi (Nature Portfolio, 2017)
Bacteria continuously inject energy into their surroundings and thus induce chaotic like flows, namely meso-scale turbulence. Here, the authors show that transition to meso-scale turbulence and inertial turbulence observed in pipes share the same scaling behavior that belongs to the directed percolation universality class.